Making a difference in language learning: the role of sociocultural factors and of learner strategy instruction. Issue 1 (1st March 2013) - Grenfell, Michael; Harris, Vee
Abstract : There has been increasing concern over the poor performance and lack of interest in modern language learning among secondary‐school students. Although there is some evidence as to the under‐achievement of boys in modern languages (ML), there is less information as to the degree to which other factors such as social class, and bilingual or monolingual status play a role; the focus of much ML research being on individual rather than sociocultural differences in language learning. The present study took place in two London schools with 120 students aged 12–13 years learning French. Using multiple regression analysis, it brings together psychological and sociocultural perspectives to examine the role of these factors on performance and motivation. In addition, it explores if these same factors are also significant in terms of students' responses to explicit instruction to teach students the strategies they need to operate autonomously. Findings suggest that at this early stage in their language learning career, there was no significant difference in terms of gender on performance or motivation but all bilingual students, regardless of whether they were in the control or experimental classes, out‐performed their monolingual peers in listening comprehension; linguistic features of their home background appeared to provide some explanation. Furthermore, the strategy instruction was also a significant factor in determining progress. The 12–13 age range may be a critical time for students, when teaching them how to learn may reverse an otherwise downward spiral in achievement and motivation.